Progress on the Kenya black rhino Action Plan (2017-2021) - Cedric Khayale; Linus Kariuki; Geoffrey Chege; Mxolisi Sibanda; Martin Mulama; Benson Okita-Ouma; Rajan Amin (Pachyderm)
Kenya conserves 75% of the eastern black rhino sub species Diceros bicornis michaeli, which is listed as Critically Endangered by the International Union for Conservation of Nature (IUCN, Emslie 2020). The species gradual recovery has been guided by a series of national five-year conservation action plans or strategies, following its dramatic decline from around 20,000 animals in the early 1970s to less than 350 by the late 1980s.